The experiencing of social support by children raised in incomplete families - Bochniarz, Agnieszka (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The family life of contemporary people is undergoing numerous changes of diverse intensity in different countries. It is because both the family model and the level of parents’ commitment in the upbringing process is changing. That is why more and more often the modern family resembles a mosaic because of its shape and its way of functioning. People raising children alone constitute an increasing part of our society. The reasons behind family’s incompleteness are numerous: death of one of the parents, divorce, abandonment, temporary absence, separated places of residence. Nevertheless, regardless of the cause, a single parent has to assume complete responsibility for the care and upbringing of the offspring, fulfil a parental role allowing material protection and take care of proper emotional bonds. Lack of one of the parents is not favourable from the point of view of the adaptation and proper development of a child. A successful solution to many of the stresses and tensions appearing in the life of a child from an incomplete family is, however, possible thanks to indirect factors which can make one immune in a way that critical events will not be taken as harmful or threatening to mental functioning, psychosocial adaptation and somatic health.
Keywords: family; single parenting; personal resources; social support